Evaluation of medication error rates in Saudi Arabia: A protocol for systematic review and meta-analysis. Issue 9 (5th March 2021) - Almalki, Ziyad S.; Alqahtani, Nasser; Salway, Najwa Tayeb; Alharbi, Mona Marzoq; Alqahtani, Abdulhadi; Alotaibi, Nawaf; Alotaibi, Tahani M.; Alshammari, Tahani
Abstract: Introduction: Due to the diversity of reports and on the rates of medications errors (MEs) in Saudi Arabia, we performed the first meta-analysis to determine the rate of medications errors in Saudi Arabia using meta-analysis in the hospital settings. Methods: We conducted a systematic literature search through August 2019 using PubMed, EMBASE, CINAHL, PsycINFO, and Google Scholar to identify all observational studies conducted in hospital settings in Saudi Arabia that reported the rate of MEs. A random-effects models were used to calculate overall MEs, as well as prescribing, dispensing, and administration error rates. The I 2 statistics were used to analyze heterogeneity. Results: Sixteen articles were included in this search. The total incidence of MEs in Saudi Arabia hospitals was estimated at 44.4%. Prescribing errors, dispensing errors, and adminstration errors incidents represent 40.2%, 28.2%, and 34.5% out of the total number of reported MEs, respectively. However, between-study heterogeneity was also generally found to be >90% (I-squared statistic). Conclusions: This study demonstrates the MEs common in health facilities. Additional efforts in the field are needed to improve medication management systems in order to prevent patient harm incidents.